Licenciamento ambiental e urbanístico dos postos de gasolina localizados no município de São Paulo: aspectos teóricos e práticos - Carvalheiro, Cláudia (2009)
Since the 1970s the number of petrol stations in Brazil has increased a lot. It s known that nowadays there are about 32.000 petrol stations working in Brazil in which 8.500 are in São Paulo state and 2.000 are in São Paulo capital. These petrol stations use underground containers to store automotive fuel and sell it afterwards. Although this is a potencially polluter activity, the establishments had never been asked by the government any kind of urban or environmental license in order to protect the environment. The situation started to change in the beginning of this decade when a law passing number 38.231/99, from São Paulo City Hall, determined the changing of the underground containers and the adequacy of the petrol stations equipments to environmental and security rules, and when a Resolution CONAMA 273/00 determined that not only the new petrol stations, but also the old ones had to have a license at the environmental organ called CETESB in São Paulo state. The importance of this subject is getting clearer as far as CETESB declared in its last report (November 2008, published in March 2009), that from 2.514 contaminated areas in the state of São Paulo, 1.953 are caused by petrol stations. Therefore, in this paper several theorical and practical issues will be mentioned about the development and implementation of a license for the new petrol stations and for the ones that are already working in São Paulo city. There will be also mentioned the interpretations and the possible solutions of the conflicts that can come from this process as well as the explanations and conclusions for each case